In situ determination of the static inductance and resistance of a plasma focus capacitor bank - Saw, S. H.; Lee, S.; Roy, F.; Chong, P. L.; Vengadeswaran, V.; Sidik, A. S. M.; Leong, Y. W.; Arwinder, Singh* (AIP Publishing, 2010)
The static (unloaded) electrical parameters of a capacitor bank are of utmost importance for the purpose of modeling the system as a whole when the capacitor bank is discharged into its dynamic electromagnetic load. Using a physical short circuit across the electromagnetic load is usually technically difficult and is unnecessary. The discharge can be operated at the highest pressure permissible in order to minimize current sheet motion, thus simulating zero dynamic load, to enable bank parameters, static inductance L0, and resistance r0 to be obtained using lightly damped sinusoid equations given the bank capacitance C0. However, for a plasma focus, even at the highest permissible pressure it is found that there is significant residual motion, so that the assumption of a zero dynamic load introduces unacceptable errors into the determination of the circuit parameters. To overcome this problem, the Lee model code is used to fit the computed current trace to the measured current waveform. Hence the dynamics is incorporated into the solution and the capacitor bank parameters are computed using the Lee model code, and more accurate static bank parameters are obtained.